Parallel dual-slot PIFA for 2.45GHz rectenna applications - Abdulkadir, Muhammad Lawan; Su, Hieng Tiong; Then, Yi Lung; Jingxin, Zhang (2018)
Energy harvesting has gained a lot of attention lately especially in the area of miniaturization where the target is smaller devices. The PIFA antenna known for its compact frame is explored here for use in Rectennas. A PIFA antenna was carefully studied and designed in this text yielding agreeable results. Going even further, a pair of slots placed in parallel with each other was included on the patch based on the concept of U-Slots. This specific technique (parallel slots) has not been recorded anywhere to the best of our knowledge. A significant improvement in return loss at the figure of about -42dB was obtained over a bandwidth of 3.02%. Subsequently, results obtained were compared without any slots and with conventional U-Slot for observation. Additionally, the theory outlined helps the reader in appreciating the opportunities offered by the PIFA both in size and possible applications.